2010
DOI: 10.1253/circj.cj-09-0664
|View full text |Cite
|
Sign up to set email alerts
|

IL-1B Polymorphism in Association With Initial Intravenous Immunoglobulin Treatment Failure in Taiwanese Children With Kawasaki Disease

Abstract: Background: Approximately 8-38% of children with Kawasaki disease (KD) will have persistent or recrudescent fever after initial intravenous immunoglobulin (IVIG) treatment and are at increased risk for development of coronary artery abnormalities. Using genetic markers may be helpful to identify the high-risk group of IVIG-resistant patients for aggressive treatment. The aim of this study was to evaluate the associations between 4 potential polymorphisms in the interleukin (IL)-1 family of genes and initial IV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(41 citation statements)
references
References 35 publications
1
38
0
Order By: Relevance
“…More recently, Fury et al demonstrated increased transcript abundance for IL-1 pathway genes in IVIG-resistant patients with KD [29]. Weng et al showed that IL-1β polymorphism was associated with initial IVIG treatment failure in Taiwanese children with KD [30]. Thus, higher IL-1β secretion and/or an IL-1β-mediated signaling pathway may be involved in the IVIG resistance in KD patients, and additional therapy by IL-1β blockade may help control the inflammation in the current IVIG-resistant patients with KD.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Fury et al demonstrated increased transcript abundance for IL-1 pathway genes in IVIG-resistant patients with KD [29]. Weng et al showed that IL-1β polymorphism was associated with initial IVIG treatment failure in Taiwanese children with KD [30]. Thus, higher IL-1β secretion and/or an IL-1β-mediated signaling pathway may be involved in the IVIG resistance in KD patients, and additional therapy by IL-1β blockade may help control the inflammation in the current IVIG-resistant patients with KD.…”
Section: Discussionmentioning
confidence: 99%
“…32,33 Treatment with infliximab might also be an initial therapy for high-risk KD patients. 25 Our previous study showed an effect of IL-1B polymorphism on the association with IVIG resistance in Taiwanese children with KD, 34 which suggests the potential usefulness of monoclonal antibodies to IL-1, such as anakinra, for IVIG-resistant patients. 35 Other immunosuppressive therapies, including cyclophosphamide, 36 methotrexate, 37 and plasma exchange, 38 have been used in the treatment of refractory KD.…”
Section: Other Treatmentsmentioning
confidence: 98%
“…IL-1β plays a critical role in broad spectrum of diseases, including chronic inflammatory diseases such as rheumatoid arthritis, metabolic syndrome, diabetes, atherosclerosis and more recently was linked to Kawasaki Disease vasculitis 25, 3641 . IL-1α also plays a critical role in chronic inflammation and studies suggest that IL-1α can regulate IL-1β secretion 37, 4244 .…”
Section: Introductionmentioning
confidence: 99%